2002
DOI: 10.1557/proc-734-b3.3
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Deformation of Glassy Polymers: Correlation Between Shear Activation Volume and Entanglement Density

Abstract: The shear activation volumes of miscible polystyrene-poly(2,6-dimethyl-1,4-phenylene oxide) (PS-PPO) blends at different PS-PPO ratios were determined experimentally by both plane strain and uniaxial compression at constant strain rates. We find that the same correlation between the shear activation volume and the entanglement density ρe holds for the blend as well as for various pure glassy polymers: . Since the shear activation volume is closely related to the size of the plastic shear zones, this correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…It is, therefore, not clear whether there should be a direct correlation between the rubber-elastic response of an entangled or cross-linked network above T g and a neo-Hookean strainhardening response below T g , except possibly at very high entanglement or network densities, such as in the case of poly(carbonate) [34]. However, the chemical cross-link density, as shown in this study, as well as the entanglement density of linear glassy polymers, as shown recently by Ho et al [35], seem to affect the viscous part of the total stress significantly, which can be accounted for by using a strain and crosslink-dependent activation volume. The importance of thermal mobility of polymer chains on strain-hardening was also recognized by van Melick et al [6].…”
Section: Cross-linked Pmmasupporting
confidence: 76%
“…It is, therefore, not clear whether there should be a direct correlation between the rubber-elastic response of an entangled or cross-linked network above T g and a neo-Hookean strainhardening response below T g , except possibly at very high entanglement or network densities, such as in the case of poly(carbonate) [34]. However, the chemical cross-link density, as shown in this study, as well as the entanglement density of linear glassy polymers, as shown recently by Ho et al [35], seem to affect the viscous part of the total stress significantly, which can be accounted for by using a strain and crosslink-dependent activation volume. The importance of thermal mobility of polymer chains on strain-hardening was also recognized by van Melick et al [6].…”
Section: Cross-linked Pmmasupporting
confidence: 76%
“…In metallic glass it is of interest to observe structural relaxation below T g which induces the embrittlement phenomenon [52,53]. The experiments have shown that many polymers present higher activation volume than metallic glasses during the deformation process [54]. Benefiting from the chemical heterogeneity of the side group and the chain backbone in macromolecules, local motion in polymers is easier than in glassy alloys.…”
Section: Stress Relaxation In La-based Metallic Glassmentioning
confidence: 99%
“…47 Although the individual material parameters in eq 9, such as size, shear strain, and activation energy of the STZ have been experimentally obtained for different MGs (see Chapter 7 of ref 16 for details), their numerical evaluation for PGs have been limited to some theoretical modeling and simulations, 16,29 and a few experimental studies. 28,30 For the conventional polymeric materials where γ T Ωτ ≫ 2k B Θ at temperatures below their glass transition temperatures, eq 8 can be reduced to…”
Section: Theory Of Homogeneous Flow For Glassymentioning
confidence: 99%